New series of 4,6-diaryl pyrimidines: facile synthesis and antiproliferative activity as dual EGFR/VEGFR-2 inhibitors - Mostafa, Yaser A.; Assoud, Jalil Abdeljalil; Desoky, Ahmed Y.; Mohamady, Samy; Mohamed, Nesma M.; Salem, Ola I. A.; Almarhoon, Zainab M.; Bräse, Stefan; Youssif, Bahaa G. M. (Frontiers in Chemistry, 2024)
We developed and produced a new series of 4,6-diaryl-pyrimidines 9-29 as antiproliferative agents targeting EGFR/VEGFR-2. The antiproliferative efficacy of the novel targets was assessed against a panel of 60 NCI cancer cell lines and four cancer cell lines in vitro. Compounds 14, 17, 19, 22, 25, and 29 demonstrated the greatest potency among the derivatives, with GI50 values between 22 and 33 nM; compounds 22 and 29 exhibited the highest potency, with GI50 values of 22 and 24 nM, respectively. We subsequently examined the most efficient derivatives as dual EGFR/VEGFR-2 inhibitors, finding that compounds 22 and 29 functioned as dual inhibitors.Moreover, 22 and 29 can act as apoptotic inducers by increasing Bax levels and decreasing levels of the anti-apoptotic protein Bcl2. At both 24-and 48-hour intervals, the cell migration rates of compounds 22 and 29 were lower than those of untreated cells, according to the migration rate and wound closure percentage assessment. The wound closure rate reached 100% after 72 hours of therapy with compound 22 but only 80% with compound 29. The docking study showed that compounds 22 and 29 had docking scores similar to those of Erlotinib and Sorafenib, cocrystallized ligands, for the EGFR and VEGFR-2 proteins. The experiments on lipophilicity showed that the new pyrimidines had a consistent result. This group of compounds has better biological activity in all the biological systems studied with low lipophilicity.